Short-Term and Long-Term Causality of the Tourism Sector on Economic Growth of OIC Member Countries - Putri Rizka Citaningati; Inayah Rahman; Sulistya Rusgianto; Kamaluddin Kamaluddin (Postgraduate Program, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
Tourism is one of the sectors affected by the Covid-19 pandemic, due to the implementation of lockdowns and social distancing in various countries around the world. Likewise with the countries that are members of the OIC. The pandemic that has hit since the end of 2019 has reduced the number of domestic and foreign tourists traveling to various tourist attractions, both domestically and abroad. This of course has an impact on slower economic growth. Therefore, using the variables of the tourism sector, inflation, foreign direct investment, and economic growth, this study aims to explain the causality of the Covid-19 pandemic on the tourism sector and the economic growth of OIC member countries. This study uses the P-VECM analysis technique to determine the short-term and long-term effects of the variables used. The results of this study reveal that the tourism sector, inflation, and foreign direct investment have short-term and long-term effects on economic growth.